Investigating Operating Modes and Converter Options of Dual Winding Permanent Magnet Synchronous Machines for Hybrid Electric Vehicles - Mese, Erkan; Yasa, Yusuf; Akca, Hakan; Aydeniz, Mustafa Gurkan; Garip, Muhammet (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
This paper investigates the operating modes and converter options of dual winding permanent magnet synchronous machines (DWPMSMs) that are used to drive accessories in hybrid electric vehicles. In this application, DWPMSM operate in three different modes: 1) motor-only; 2) generator-only; and 3) simultaneous motor-generator modes. Motor-only and generator-only operations can be treated independently as long as two winding sets are magnetically decoupled. Simultaneous motor-generator mode links two winding sets through a mechanical shaft. As part of this study, the impact of dual winding set usage on the machine's output and performance is also investigated. Experimental results are given for each mode. The converter options of generator winding were investigated as well. These options include uncontrolled rectifier with dc-dc converter and controlled rectifier. Two converters are compared for their impacts on efficiency and generator current harmonics. The relationship between speed and converter control variable is given for various back electromotive force constant values of the DWPMSM.
Keywords: Concentrated winding; controlled rectifier; dual winding permanent magnet synchronous machines (DWPMSM); electric accessory drive system (EADS); hybrid electric vehicle (HEV); uncontrolled rectifier; GENERATION; MOTOR; Energy & Fuels; Engineering